1984
DOI: 10.1002/cne.902290305
|View full text |Cite
|
Sign up to set email alerts
|

The morphology and distribution of neurons containing choline acetyltransferase in the adult rat spinal cord: An immunocytochemical study

Abstract: A monoclonal antibody to choline acetyltransferase (ChAT), the acetylcholine (ACh)-synthesizing enzyme, has been used to localize ChAT within neurons in immunocytochemical preparations of adult rat spinal cord. Morphological details of known cholinergic spinal neurons are presented in this study, and previously unidentified ChAT-containing neurons are also described. Immunoreaction product was present within cell bodies, dendrites, axons, and axon terminals, thereby allowing comprehensive descriptions of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
205
1
7

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(242 citation statements)
references
References 63 publications
29
205
1
7
Order By: Relevance
“…We found that the YFP ϩ /NOS Ϫ neurons, which likely give rise to the C boutons, are lateral to the central canal and show strong ChAT immunoreactivity. This profile identifies them as belonging to the medial group of partition neurons (33). Interestingly, YFP was not present in all of the strongly ChAT ϩ neurons in this region, suggesting that the C boutons originate from a specific subpopulation of medial partition cells that express Dbx1 at some stage during their development.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We found that the YFP ϩ /NOS Ϫ neurons, which likely give rise to the C boutons, are lateral to the central canal and show strong ChAT immunoreactivity. This profile identifies them as belonging to the medial group of partition neurons (33). Interestingly, YFP was not present in all of the strongly ChAT ϩ neurons in this region, suggesting that the C boutons originate from a specific subpopulation of medial partition cells that express Dbx1 at some stage during their development.…”
Section: Discussionmentioning
confidence: 94%
“…Several groups of cholinergic interneurons have been identified in the spinal cord (33). In addition to autonomic neurons (which are present at thoraco-lumbar and sacral levels), there are scattered neurons in the dorsal horn, cells that surround the central canal (central canal cluster cells), and a population of neurons that occupy a region extending from lamina X to the lateral edge of the gray matter.…”
Section: Discussionmentioning
confidence: 99%
“…ChAT is a marker of cholinergic motoneurons and interneurons, 46 while HSP-27 labels motoneurons only. 47 There were approximately 30 neurons per section stained with HSP-27, whereas ChAT-labeled sections averaged around 60 neurons per section.…”
Section: Fos In Lamina IXmentioning
confidence: 99%
“…SPNs and motoneurons are known to be cholinergic and contain the acetylcholine synthetizing enzyme ChAT. 25,55,56 One limitation of this study is the small number of cases that we were able to investigate. Although we examined only three human cases, we were able to detect degenerative changes within the speci®c neuronal population of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%